PENGARUH MODEL CONCEPT SENTENCE TERHADAP KETERAMPILAN MENULIS SISWA KELAS III SEKOLAH DASAR - Emilia Emilia; Siti Halidjah; Hery Kresnadi (Universitas Tanjungpura, 2021)
AbstractThis study aims to analyze the application of the concept sentence modelto the writing skills of third grade students of Elementary School 03Pontianak Kota. The experimental method is a quasi experimentaldesign, and the design is nonequivalent control group design. The studypopulation was 59 students. Data collection techniques usingmeasurement techniques. The instrument used was a 3-question essayresult test sheet. Based on the calculation, the average post-test result forthe control class is 72.88 and the average post-test result for theexperimental class is 79.30 so that the post-test data tcount is 3.587 witht table for significance level α = 5% and dk = 60 is 1.673, becausetcount> ttable, then Ha is accepted, this proves that there is an effect ofthe concept sentence model on the writing skills of third grade students ofPublic Elementary School 03 in Pontianak City. The effect size is 0.66, sothe concept sentence model has a moderate effect on the writing skills ofthe third grade students of Elementary School 03 Pontianak Kota.Keywords: Concept Sentence Model, Influence, Paragraphs, Writing Skills.